Livelihood Restoration Satisfaction of the Resettlement People in Mekong-Xayabury Hydroelectric Power Project - Keotha, Phouvakone; Phoumphon, Keopheth; Dansavan, Khamtun (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This paper is a study on the livelihood restoration satisfaction of the resettlement people in the Mekong- Xayabury Hydroelectric Power Project. The objectives of the study are to examine the family’s income restoration activity satisfaction, the satisfaction of the family's income gained, and the satisfaction with the livelihood of the resettlement families in the new village. The research instrument of this study was the interview form; the researcher of this study interviewed all resettlement families in the total of 76 in Natongai village, Xayabury district, Xayabury province. Program SPSS was employed to calculate the data. The finding found that the resettlement families have positive satisfaction with the family’s income activities restoration with M=4.17; Std= 0.575 at 95% confidential interval. The families have positive satisfaction with the family’s income gained M=4.15 and Std= 0.655 at 95% confidential interval, and the resettlement families have positive satisfaction with the livelihood in the new resettlement village at 95% confidential interval.